Elucidation of relaxin-3 binding interactions in the extracellular loops of RXFP3 - Bathgate, Ross; Oh, Maria; Ling, Jason; Kaas, Quentin; Hossain, Akhter; Gooley, Paul; Rosengren, Johan (Frontiers in Endocrinology, 2013)
Relaxin-3 is a highly conserved neuropeptide in vertebrate species and binds to the Class A G protein-coupled receptor RXFP3. Relaxin-3 is involved in a wide range of behaviours, including feeding, stress responses, arousal and cognitive processes and therefore targeting of RXFP3 may be relevant for a range of neurological diseases. Structural knowledge of RXFP3 and its interaction with relaxin-3 would both increase our understanding of ligand recognition in GPCRs that respond to protein ligands and enable acceleration of the design of drug leads. In this study we have used comparative sequence analysis, molecular modelling and receptor mutagenesis to investigate the binding site of the native ligand human relaxin-3 (H3 relaxin) on the human RXFP3 receptor. Previous structure function studies have demonstrated that arginine residues in the H3 relaxin B-chain are critical for binding interactions with the receptor extracellular loops and/or N-terminal domain. Hence we have concentrated on determining the ligand interacting sites in these domains and have focussed on glutamic (E) and aspartic acid (D) residues in these regions that may form electrostatic interactions with these critical arginine residues. Conserved D/E residues identified from vertebrate species multiple sequence alignments were mutated to Ala in human RXFP3 to test the effect of loss of amino acid side chain on receptor binding using both Eu-labelled relaxin-3 agonist. Finally data from mutagenesis experiments have been used in ligand docking simulations to a homology model of human RXFP3 based on the peptide-bound CXCR4 structure. These studies have resulted in a model of the relaxin-3 interaction with RXFP3 which will inform further interrogation of the agonist binding site.